The Impact of Animated Silent Movies on Students’ Speaking Achievement: An Experimental Study - Berlian Cantika Candra; Endang Mastuti Rahayu (Universitas Galuh, 2026)
Many students face difficulties in developing English speaking skills due to limited practice opportunities and unengaging instructional media. Although silent movies have been widely used in language learning, most previous studies have focused on writing skills, leaving their impact on speaking achievement underexplored. Therefore, this study aimed to examine the impact of using silent movies on students’ speaking achievement at SMA Ta’miriyah Surabaya. This study employed a true experimental design with a pre-test and post-test control group. The population consisted of 121 twelfth-grade students in the 2025/2026 academic year. Two classes were selected through cluster random sampling, i.e., class XII-1 as the experimental group, which was taught using animated silent movies, and class XII-3 as the control group, which used non-animated silent movies. Speaking achievement was measured through performance-based tests and analyzed using an independent samples t-test with SPSS version 25. The results showed that the experimental group achieved significantly higher post-test scores than the control group (p < 0.05), indicating that students taught using animated silent movies outperformed those in the control group. This finding demonstrates that silent movies have a significant positive impact on students’ speaking achievement. Therefore, silent movies can be used as an effective instructional medium to enhance speaking skills and support engaging learning in EFL classrooms.